INVITRO ANTIVIRAL SCREENING OF PSIDIUM GUJAVA L AGAINST HSV-1 AND HSV-2 BY CPE INHIBITION ASSAY - Anjana.A.K; Francis, Prasanth; Gomathy.S; Soumya.K.Vijayan; Mohammed, Manal; Chandrasekar, M.J.N (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: Herpes simplex virus (HSV) type 1 & 2 are most infectious pathogens for humans, especially in the case of highly susceptible adults. After establishing latency, HSV can reactivate, causing frequent recurrent infections in some patients, while most people experience few recurrences. The increase in viral infections and the prevalent resistance of virions to chemotherapeutic agents urges us to search for an efficient and novel antiviral strategy. Traditionally leaf paste of Psidium gujava L. was used to treat acne, ulcers, cholera, nephritis etc. Psidium gujava L. has been reported for its antimicrobial, antioxidant and antidiabetic potentials. Methods: Plant leaves collected in and around Malappuram District of Kerala, India, were extracted by continuous extraction and cold maceration techniques. The selection of extracts made according to the data obtained from phytochemical screening. Cytotoxicity assays such as MTT and SRB were performed to find out the cytotoxic tolerance limits for dose calculation. The plant extracts were screened for its antiviral property by CPE inhibition assay against various virus challenge doses such as 2TCID50 and 10TCID50. Results: Pet. ether extract showed significant activity in lower doses such as 50µg/ml, 100 µg/ml (2TCID50) and 100 µg/ml (10TCID50). The hydro alcoholic (Soxhlet extraction & maceration) extracts also showed partial activity. Conclusion: All the extracts were showing its potential to inhibit both HSV-1 and HSV-2 proliferation in Vero cells. Further research is needed to elucidate the active constituents of this plant which may be useful in the development of new and effective antiviral agents. Keywords: Psidium Gujava L, Herpes simplex virus, CPE Inhibition assay, Cytotoxicity.